Tracheostomy Wound Myiasis in a Child: Case Report and Review of the Literature - J. Blejter (Case Reports in Pediatrics)
An 8-year-old tracheostomized, gastrostomized, and with cerebral palsy boy was admitted for tracheostomy wound myiasis and cellulitis. Ether was applied in the wound, and then all the accessible larvae were removed. Antibiotic therapy was initiated. The procedure had to be repeated three more times to extract all the larvae. An airway endoscopy was performed and ruled out the presence of larvae in the airway, as well as any damage to the wall of the trachea. The patient recovered uneventfully and was discharged.